Excess Volumes Mixing for Binary Liquid Mixtures of n-Hexane with Chloro Alkanes - Gupta, A.K.; Yadav, C.K.; Ansari, A.S. (Asian Journal of Chemistry, 2010)
Excess volumes of mixing (VE) for binary liquid mixtures of n-hexane with ethylene dichloride, methylene dichloride, methylene chloride, chloroform and carbon tetrachloride have been meausred dilatometrically at temperatures 283.15 K, 293.15 K and 303.15 K. Volume excess of all these mixtures has been found to be positive in sign at entire mole-fraction range. The temperature coefficients for equimolal mixtures have been found to be positive.